EFEK KONSUMSI SARI ANTOSIANIN BUAH TOMI-TOMI (FLAUCORTIA INERMIS ROXB.) PADA KELILING JANTUNG MENCIT DISLIPIDEMIA - Muninggar, Jodelin -; Lestario, Lydia Ninan (Jurnal Pendidikan Teknologi Informasi (JUKANTI), 2019)
The aim of this research was to determine the effect of giving anthocyanin extract of tomi-tomi fruit at various dosage on hearth circumference of mice. The research was done by giving high fat feed to 18 mice aged 6 months for 14 days, then the mice were divided into 6 groups, 4 groups were given anthocyanin extract with multilevel dosage 1-4 (13,75mg/kgbw; 27,95mg/kgbw; 41,925 mg/kgbw; 55,9mg/kgbw) for 21 days, 1 group as negative group, and 1 group as control positive with Simvastatin 10 mg. After that, the mice were terminated, and the heart was processed to microscope preparatsliced by Hematoxylin Eosin staining, then the heart circumference was measured. The result showed that heart circumference of negative group was 11.483±940,0?m; control positive group was 12.227±834,5?m; whereas groups with anthocyanin consumption extract were 14.360±694,0?m (dosage1); 20.001±1592,0?m (dosage2); 16.412±924,0 ?m (dosage3); and 11.904±813,5?m (dosage4). Statistical analysis by One Way ANOVA showed that there were significant difference between treatment groups (p=0,04). Post Hoc LSD showed that dose 2 anthocyanin was the most significans compared to other groups (p=0,01). Spearman's correlation showed moderate correlation (p=0,162; r=0,412) between dosage of anthocyanin with heart circumference of mice. It can be concluded that anthocyanin extract consumption of tomi-tomi fruit to improve of dyslipidemia mice heart circumference. Dosage 27,95mg/kgbw could maximally improve structure of it, than Simvastatin 10mg effects.